SOME ISSUES OF THE FORMATION OF PUBLIC EDUCATION IN KHOREZM AT THE BEGINNING OF THE 20TH CENTURY (TAMADDUN NURI JURNALI, 2024)
This article analyzes the development of public education in Khorezm at the beginning of the 20th century, the introduction of the Soviet education system instead of traditional schools in the oasis. The article talks about the sovietization of the education system and its impact on socio-political life.